Detecting the protein inhibitor of polygalacturonase in banana - Thắng, Nguyễn Tiến; Hiệp, Đinh Minh; Bulanseva, EA; Protsenko, MA (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 67-72, 2005